A família como fator de apoio à aquisição da libras por crianças surdas - Silva, Pedro Henrique de Macedo (2021)
This work aims to critically reflect on the importance of the role of deaf children in the acquisition of the Brazilian Sign Language (Libras). This topic is of interest to the deaf community, teachers, psychopedagogists and researchers who work in teaching Libras in Brazil. Although there is a robust theoretical framework on the origin and evolution of this language, as well as on its teaching-learning by deaf people, it is necessary to investigate more closely the role of the family, or rather, the encouragement and performance of family members of deaf children in learning this language. language, as well as the Portuguese language, since it is common ground that the success of learning is supported by the development of bilingualism. An important discussion in which this study is inserted is to understand how the family of deaf children can play a decisive role in the process of acquiring pounds, through specific studies (field research or case study) with deaf adults and their families. The report of deaf adults and their families can help to clarify the difficulties and obstacles faced in acquiring Libras, including in the family nucleus. Historically, deaf people have always been treated as people with disabilities and not as individuals with differences in hearing, but who are able to learn Libras. This scenario began to change through the efforts of educators and philosophers in the construction of Sign Language and in demystifying the total incapacity of the deaf to learn not only Libras, but also the Portuguese language. However, for this to be fully effective, family support in the deaf child's learning, from an early age, is essential, as it is the parents, grandparents, in short, the closest family members who provide the basis for learning several essential things for life, who educate the world and who decide for the children, since they do not have the maturity for any decision-making power when they are small. Thus, the view that family members, especially parents, have about Libras is important, as from then on they will be interested in learning and making their children learn the Brazilian Sign Language. It is so true that studies on this topic have shown that in addition to the role of parents being essential for the acquisition of sign language by deaf children, the sooner this is accomplished, the smaller the difficulties faced by children in developing sign language, acquire the oral language and also the Portuguese language. For the deaf child, the internalization of this entire process also depends on the parents and their commitment to their children's learning. However, in practice this is not always effective and deaf children end up being harmed in the future, as the number of deaf people who reach adolescence in Brazil is significant and enter the school system without knowing any language. All these issues were discussed in this study, which also made a historical journey about the origin and evolution of sign language in the world and in Brazil and its importance for the communication, socialization and learning of the deaf community, the theories that have emerged around the teaching-learning of Sign Language, as well as the legal recognition of Libras in Brazil and its practical effects on the educational educational system. In addition to the theoretical support, which is robust in relation to these aspects associated with sign language, a field research was carried out with deaf adults and their families in order to gather information on the role of the family in the acquisition of pounds, through an interview and application two questionnaires, one for parents and one for deaf adults, with closed and open questions. Thus, the data collection instrument was the semi-structured interview together with the video recording of the interviewees, whose population sample consisted of 20 people (10 deaf adults and 10 family members). Based on the results of this research, a theoretical clash was made with the scientific publications mentioned in the study, in order to draw a comparison with the findings of this research and, as a partial result, we could see that the family in fact plays a very important role in the process of acquiring Libras , as the deaf who did not have family support from an early age were precisely the ones who had contact with this language later and who faced greater difficulties in the process of communication with family members and with the outside world, including with regard to their professionalization future. Deaf people who have had support from family members since childhood, whether by encouraging the acquisition of pounds, or also learning their own language to communicate with their children, thus achieving greater success in teaching and learning the language, as well as in the construction of deaf identity and culture.